IMPACT OF NON-SKID SOCKS AND ANTERIOR WEIGHT ON POSTURAL RESPONSE AND STABILITY DURING PERTURBATION - Acuna, Juaquin; Kiphen, Briana; Lee, Alexander; MacKinnon, Amanda; Manese, Liz; Ngo, Austin; Oberhammer, Nicole; Tran, Tommy; Truong, Ethan; Shiraishi, Michael; Moon, Seong Hyun; Rajagopal, Sivakumar; et al. (Biomedical sciences instrumentation, 2025)
Non-skid socks and external weight are commonly utilized in healthcare and training to improve stability and simulate real-world conditions. However, their combined effects on postural response during perturbation remain unclear. This study examined how non-skid socks and added anterior weight affect latency and amplitude responses during postural perturbations. Ten healthy participants (mean age 24.5 ± 4.38 years) underwent randomized perturbation conditions with and without non-skid socks and 10% body weight applied via weighted vests. Results from two-way ANOVA and mixed-effects models revealed no significant effects of socks, weight, or their interaction on latency (p > 0.05). However, amplitude analysis showed a significant interaction (p < 0.001), indicating that the combination of socks and weight increased postural instability. Specifically, conditions involving non-skid socks and weight resulted in higher amplitudes, suggesting greater deviations of the center of gravity and increased fall risk. Conversely, non-skid socks alone reduced amplitude, enhancing stability compared to barefoot conditions. These findings highlight the nuanced effects of non-skid socks and added weight on balance and stability. While socks alone may improve postural control, their combination with weight appears to elevate instability. Future research should include larger, diverse samples to confirm these findings and guide clinical practice regarding non-skid socks and weighted training protocols.